Emergence of tigecycline- and eravacycline-resistant Tet(X4)-producing Enterobacteriaceae in the gut microbiota of healthy Singaporeans. (27th August 2020) - Ding, Yichen; Saw, Woei-Yuh; Tan, Linda Wei Lin; Moong, Don Kyin Nwe; Nagarajan, Niranjan; Teo, Yik Ying; Seedorf, Henning
Abstract: Objectives: The recently discovered tigecycline-inactivating enzyme Tet(X4) can confer high-level tigecycline resistance on its hosts, which makes it a public health concern. This study focused on isolation and screening of Tet(X4)-positive Enterobacteriaceae from the gut microbiota of a cohort of healthy individuals in Singapore. Methods: MinION and Illumina sequencing was performed to obtain the complete genome sequences of Escherichia coli 2EC1-1 and 94EC. Subsequently, 109 human faecal samples were screened retrospectively for eravacycline-resistant Enterobacteriaceae strains, which were further tested for tet (X4) by PCR. The taxonomy of the isolated strains was determined by 16S rRNA gene PCR and Sanger sequencing. Results: Comparative genomic analysis of E. coli 2EC1-1 and 94EC revealed that both carry tet (X4), which is encoded by IncI1-type plasmids p2EC1-1 and p94EC-2, respectively. Retrospective screening of faecal samples collected from 109 healthy individuals showed that the faecal carriage rate of Tet(X4)-producing Enterobacteriaceae is 10.1% (95% CI = 5.1%–17.3%), suggesting that tet (X4) is widely distributed in the gut microbiota of healthy individuals in Singapore. Conclusions: To the best of our knowledge, this is the first report on the prevalence of tet (X4) in the gut microbiota of a healthy human cohort, as well as the first description of this resistance mechanism outside of China. Our findings suggest that surveillance of tet (X4) in community settings is vital to monitor the spread of this resistance mechanism.